EuroBrake 2021 Technical Programme 2021
DOI: 10.46720/7783060eb2021-stp-020
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Comparisons of Particulate Emissions Generated from Different Disc Brake Rotors

Abstract: Lightweight disc brake rotors have become a popular alternative to conventional grey cast iron (GCI). The thermal and tribological response of these brake rotors will differ during a braking operation. This may result in the generation of particulate wear debris with different characteristics, which can affect the environment and human health to different degrees. Studies have shown a relationship between adverse health effects and the characteristics of airborne particulate matter such as particle size, conce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 11 publications
(13 reference statements)
2
2
0
Order By: Relevance
“…The present study shows that, as the brake pressure increases, the particle mass emissions decrease. A similar study carried out by Asmawi et al [30] found that the particle mass emissions in the PM10 category also decreased as the brake pressure increased. This decreasing particle mass with the increase of brake pressure could be attributed to the reduction in COF at higher brake pressures which was also reported by Asmawi et al [30].…”
Section: Brake Pad Wear Loss Measurementssupporting
confidence: 54%
See 3 more Smart Citations
“…The present study shows that, as the brake pressure increases, the particle mass emissions decrease. A similar study carried out by Asmawi et al [30] found that the particle mass emissions in the PM10 category also decreased as the brake pressure increased. This decreasing particle mass with the increase of brake pressure could be attributed to the reduction in COF at higher brake pressures which was also reported by Asmawi et al [30].…”
Section: Brake Pad Wear Loss Measurementssupporting
confidence: 54%
“…A similar study carried out by Asmawi et al [30] found that the particle mass emissions in the PM10 category also decreased as the brake pressure increased. This decreasing particle mass with the increase of brake pressure could be attributed to the reduction in COF at higher brake pressures which was also reported by Asmawi et al [30]. The influences of the tribolayer not only affects the braking performance but also the formation of surface corrosion.…”
Section: Brake Pad Wear Loss Measurementssupporting
confidence: 54%
See 2 more Smart Citations